Blister-based laser-induced forward transfer of 1D and 2D carbon nanomaterials. (July 2020) - Dezhkina, M.A.; Komlenok, M.S.; Pivovarov, P.A.; Rybin, M.G.; Arutyunyan, N.R.; Popovich, A.F.; Obraztsova, E.D.; Konov, V.I.
Abstract: The possibility of laser printing of single-walled carbon nanotubes (SWCNTs) and graphene via blister-based laser-induced forward transfer technique is demonstrated. Laser radiation with optimized fluence, that is absorbed in a thin aluminium film, causes its local evaporation and blistering without rupture, which leads to the ejection of carbon nanomaterial from the donor to the receiving substrate. The use of preliminary cutting of the donor layer into square pixels allows printing SWCNTs while maintaining their shape. Raman analysis indicates the transfer of carbon nanomaterials without significant degradation.